Magnesium orthostannate (Mg2Sn04) - based thermally stable capacitor components - Ahmad Taha, Iftetan; Shaari, Abdul Halim; Wan Yusoff, Wan Mohamad Daud (Universiti Putra Malaysia Press, 2002)
The alkaline-earth stannates having the general chemical formula MSn03 (M = Ca, Sr and Ba), have been projected as potential electronic ceramics (thermally stable capacitors, humidity sensor, carbon dioxide sensor, etc.). Even though magnesium is from the same group, no reliable technical information on the compounds in the MgO - Sn02 system. The aim of this study is to thoroughly study the system via solid state route (SSR) with respect to synthesis, processing and characterization - structural, microstructural and electrical. A thorough analyses of the as measured electrical data showed that, the material possessed a very weak temperature dependence of capacitance (TCC) in the range of 25 - 300 Cover several decades of frequency. Thus holding the promise to its usage as thermally stable component in high - speed computing devices, where temperature is prone to increase due to fast electronic transition and inefficient heat dissipation in smaller volume due to miniaturisation of future devices.